Is It Me or You?—How Reactions to Abusive Supervision Are Shaped by Leader Behavior and Follower Perceptions - Schyns, Birgit; Felfe, Jörg; Schilling, Jan (Frontiers in Psychology, 2018)
There is a growing interest in understanding how follower reactions towards abusive leadership are shaped by followers’ perceptions and attributions. Our studies add to the understanding of the process happening between different levels of leaders’ abusive behavior (from constructive leadership as control, laissez-faire, mild to strong abusive) and follower reactions. Specifically, we focus on the role of perception of abusive supervision as a mediator and attribution as a moderator of the relationship between leader abusive behavior and follower reactions. Follower reactions are defined in terms of exit, voice, loyalty, and neglect. Two studies using a two point experimental design and vignettes and a cross-sectional field study were conducted. Perception partly mediates the relationship between leader behavior and reactions (Study 1 and 2). Different attributions (intention, control) moderate the relationship between the perception of abusive supervision and reactions in Study 2 and 3. In Study 2, attribution of intentionality of the leader behavior served as a moderator of the relationship between abusive supervision and loyalty, turnover, and voice. Attribution of intentionality reduced the relationship between perception of abusive supervision and reactions. Attribution of intentionality only strengthened negative reactions when milder abusive leadership was perceived. These results were not supported in Study 3. However, in Study 3, attribution to the supervisor’ control served as moderator for loyalty and voice. A stronger relationship between the perception of abusive supervision and reactions emerged for high versus for low attribution to the supervisor. The differences in results between the studies reflect that in Study 1 and 2 abusive behavior was manipulated and in Study 3 the perception of abusive supervision of actual leaders was assessed. Our findings show that avoidance of abusive supervision should be taken seriously and followers’ perception and suffering is not only due to subjective judgment but reflects actual differences in behavior. The relationships are stronger in the field study, because, in practice, abusive behaviors might be more ambiguous. The research presented here can help leaders to better understand their own and the followers’ role in the perception of and reaction to abusive supervision.